A family with mental disorder as the first symptom finally confirmed with Gerstmann–Sträussler–Scheinker disease with P102L mutation in PRNP gene – case report. Issue 1 (31st December 2023) - Chen, Zeran; Guo, Junjun; Ran, Ningjing; Zhong, Yujia; Yang, Fang; Sun, Honghui
ABSTRACT: Gerstmann–Sträussler–Scheinker (GSS) disease is an autosomal dominant neurodegenerative disease, and it is characterized by progressive cerebellar ataxia. Up to now, GSS cases with the p.P102L mutation have mainly been reported in Caucasian, but rarely in Asian populations. A 54-year-old female patient presented with an unstable gait in the hospital. Last year, she was unable to walk steadily and occasionally choked, could not even walk independently gradually. After taking her medical history, we found that she was misdiagnosed with schizophrenia before the gait problems. The patient's father showed similar symptoms and was diagnosed with brain atrophy at the age of 56, but her daughter showed no similar symptoms at present. On arrival at the Neurology Department, the patient's vital signs and laboratory examinations showed no abnormality. As the proband presented with cerebellar ataxia and had an obvious family history, we were sure that she had hereditary cerebellar ataxia. Then, patient's brain MRI showed an abnormal signal in the right parietal cortex and bilateral small ischaemic lesions in the frontal lobe. A gene panel (including 142 ataxia-related genes) was performed, and a heterozygous mutation PRNP Exon2 c.305C>T p. (Pro102Leu) was identified. Her daughter had the same heterozygous mutation. The patient was diagnosed with GSS with mental disorders as initial symptoms. After 2 months of TCM treatment, the patient's walking instability decreased, and her emotional fluctuations were less than before. In conclusion, we have reported a rare case of GSS in Sichuan, China, and the family with mental disorder as the first symptom was finally confirmed with GSS PRNP P102L mutation.